Lived Experiences of Parents Caring for Children and Adolescents with Autism Spectrum Disorder in Eswatini - Thulani Ricardo Nhlabatsi; Motshedisi Boitumelo Sabone (KHD-Production, 2024)
Autism spectrum disorder (ASD) is a neuro-developmental disorder the rate of which has escalated to a global concern. Caring for a child with ASD is associated with a myriad of challenges for parents, who often lack support and practical assistance. However, there is paucity of research on the experiences of parents caring for children with ASD in Eswatini. Therefore, this study describes the lived experiences of parents caring for children and adolescents with ASD in Eswatini. Ten parents caring for children and adolescents with ASD were purposively sampled and engaged in in-depth individual interviews. Data were subjected to content analysis to uncover parents’ lived experiences. Findings revealed that providing care to children and adolescents with ASD was challenging to parents, who usually had neither the knowledge of what they were dealing with, nor the resources for caregiving. In addition, the journey to the diagnosis of ASD tended to be long and anxiety-laden. On a positive note, parents viewed the caring experience as their portion from God; and therefore, appreciated their children as gifts from God deserving of love. Although they appreciated some degree of support from within the family and from outside the family, parents expressed a dire for financial and welfare, educational, and health care support. Caring for a child/adolescent with ASD is a 24 hours-a-day and 7-days-a-week journey, characterized by daily frustrations and a yearning for instrumental and emotional support. Parents need empowerment through programme and policy in order that they can fulfil the demands of caregiving.